Glaciological Monitoring Using the Sun as a Radio Source for Echo Detection. Issue 14 (14th July 2021) - Peters, S. T.; Schroeder, D. M.; Chu, W.; Castelletti, D.; Haynes, M. S.; Christoffersen, P.; Romero‐Wolf, A.
Abstract: Ice‐penetrating radar observations are critical for projecting ice‐sheet contribution to sea‐level rise; however, these prognostic models have significant uncertainties due to an incomplete understanding of glacial subsurface processes. Existing radars that can characterize subsurface conditions are too resource‐intensive to simultaneously monitor ice sheets at both the necessary temporal—daily to multiannual—and spatial—tributary to continental—scales. Here, we investigate using an ambient radio source, instead of transmitting a signal, for glaciological monitoring. We demonstrate, for the first time, passive radio sounding using the Sun to accurately measure ice thickness on Store Glacier, Greenland. Passive radar sounding could provide low‐resource time‐series measurements of the cryosphere, enabling us to observe and understand evolving englacial and subglacial conditions across Greenland and Antarctica with unprecedented coverage and resolution. Plain Language Summary: Traditional ice‐penetrating radars transmit a powerful electromagnetic pulse and record the echo's delay time and power to measure ice sheet thickness and subsurface conditions. While active radar sounding is the principle remote sensing technique used to observe the subsurface of Greenland and Antarctica, existing radar systems are resource‐intensive in terms of cost, power, and logistics when simultaneously monitoring ice sheets at both their evolving temporal (daily to multiannual) and spatial (tributary to continental) scales. However, these observations are critical as ice sheet contribution to sea‐level rise presents one of the greatest challenges our society faces in the next century. We address this challenge by developing a novel, low‐resource, passive radar sounding technique that uses ambient radio signals from the Sun to observe the subsurface of ice sheets at these spatiotemporal scales, instead of transmitting its own powerful radio signal for echo detection. We first demonstrate passive radio sounding using the Sun to accurately measure ice thickness on Store Glacier, Greenland. We then evaluate the passive radar's performance and ability to provide valuable glaciological observations, such as melt rates, bed reflectivity changes, and englacial water storage that have traditionally been obtained using active radar systems but never passively. Key Points: We demonstrate a novel "passive" radar sounding approach using the Sun as a radio source to measure ice sheet thickness for the first time We evaluate the passive radar's potential to provide continuous records of ice thickness changes, basal conditions, and subsurface processes This demonstration charts a course for the development of low‐resource, continuous and pervasive monitoring of glacier subsurface conditions